Bridging Tradition and Islamic Law: The Evolution of Pakpak Customary Inheritance Practices in the Muslim Community of Dairi - Gajah, Sufi Maulana; Irwan; Dahruji (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2025)
Background: The evolution of inheritance practices within the Pakpak Muslim population in Dairi indicates a progressive transition from traditional to Islamic inheritance law (Faraidh). Historically, Pakpak customary law favored male heirs, precluding daughters from inheriting real property. Increased legal understanding, discussions on gender equality, and marrying with non-Pakpak persons have prompted the community to accept Islamic inheritance principles voluntarily Purpose: This study examines the factors behind this change and assesses its ramifications via the lenses of Living Law Theory, Legal Awareness Theory, and Maqasid al-Shariah Methods: Utilizing a qualitative case study with a normative-empirical framework, data were gathered via interviews with traditional leaders, religious authorities, and community members. Results: The results indicate that Islamic inheritance law is regarded as more equitable and consistent with religious duties and changing societal standards. The transition transpires spontaneously through musyawarah (family deliberation) and religious influence rather than state-imposed legal reform. The research enhances the dialogue on Islamic legal pluralism by illustrating the coexistence and evolution of customary and Islamic legal systems. Implication: The findings hold practical significance for policymakers and religious organizations, highlighting the necessity of legal awareness initiatives and community-oriented law adjustments to promote gender justice and equitable inheritance distribution Originality: comparative analysis of Malaysia's shift from Adat Temenggong inheritance to Faraidh, emphasizing how voluntary, community-driven transformation might be an alternative to state-mandated legal reform